Mechanical Strength and Degree of Polymerization of Oil-paper Non-wood Kenaf Bast Fiber as New Transformer Insulation Presspaper - Nurul `Izzati, Hashim; Mohd Taufiq, Ishak; Mohd Taufik Jusoh, Tajudin; Ja'afar, Adnan; Anis Shahida Niza, Mokhtar; Nur Sabrina, Suhaimi; Nadira, Johari Halim Shah Ayob
Growing populations and the lack of wood fiber have led to exploring non-wood fibers as alternatives for presspapermanufacturing, aiming to supplement the limited wood fiber resources. The Kenaf plant is one of the potential alternatives for these purposes. The aim of this study is to investigate the ageing characteristics of non-wood Kenaf fiber to assess its suitability for use as a new presspaper insulation in transformer. Kenaf presspaper was produced through soda pulping and laboratory handsheet process. Tensile strength (TS) and degree of polymerization (DP) assessments were conducted in according to TAPPI T494 and IEC60450 standard to measure the changes of degradation characteristic on Kenaf presspaper. The accelerated aging process at 90 °Cup to 720 hours was done to simulate extended real operation of transformer. The results indicated a reduction in both the TS and DP of Kenafpresspaper (KP) with increased aging time. The relationship between DP and TS revealed consistent decreases over aging time due to the formation of cross-links between polymer chains during ageing, contributing to the overall deterioration of the fiber's mechanical integrity.